LA FRUSTRATION IDENTITAIRE. QUELQUES IDÉES DE MIHAI MITREA-CELARIANU SUR L’ÉCOLE ROUMAINE DE COMPOSITION - Luana STAN (Studia Universitatis Babeş-Bolyai. Musica)
Mihai Mitrea-Celarianu was a French-Romanian composer. Born in Bucarest in 1935, after the arrival of the communist regime, he was forced to leave the country and he installed himself in Paris, where he died in 2003. His way of writing music was largely influenced by the modern western music, the New Cinema and the New Novel (Alain Robbe-Grillet, Alain Resnais), the serialism, Karlheinz Stockhausen and the dreams theory. After the Romanian revolution (1989), many composers tried to express their point of view about the existence or the absence of a “Romanian music school” and so often, their opinion was influenced by their own situation as expatriate people in different occidental countries. This interview was taken in Paris, on the 14th of December, 1999.